Is Indonesia’s Company Law Ready to Turn the Page on Outdated Liquidation Procedures? - Waisapi, Jeffry Yuliyanto (Journal of Law and Legal Reform, 2024)
Business practices in Indonesia increasingly rely on Limited Liability Companies (LLCs), which are central to various sectors, including trade, industry, finance, and insurance. Liquidation, the process of dissolving an LLC and settling its assets, plays a critical role when a company ceases operations. This study examines the legal framework governing LLC liquidation under Law No. 40 of 2007 on Limited Liability Companies (UUPT), using a normative juridical approach. It highlights the liquidator’s role in the dissolution process, grounded in Article 1233 of the Indonesian Civil Code, which outlines that legal relationships arise from consent or law. Upon liquidation, the liquidator assumes responsibility for managing the company’s assets and liabilities, as mandated by Article 149, paragraph (1) of the UUPT. The liquidator’s duties include collecting assets, notifying creditors, publishing liquidation notices in newspapers and the State Gazette, and distributing remaining funds to shareholders. The liquidator must also provide a final report to the General Meeting of Shareholders (GMS) or the court for approval. Once the report is accepted, the LLC is formally dissolved and ceases to exist as a legal entity. This study reveals the need for reform in the liquidation procedures, emphasizing the complexity of managing the dissolution process in today’s interconnected business environment. With evolving commercial dynamics, the current legal framework may require updates to streamline liquidation and ensure more effective resolution for all stakeholders involved.